The collective innovative process in intermediate graphic representation in the early stage of the design process: towards a conceptual framework for improving the collective exploration of innovation. (30th October 2007) - Stoeltzlen, Nadine; Roussel, Benoit; Vallette, Thomas
In order to improve the early stages of the design process, the process in which we are involved sets up the implementation of a multidisciplinary team project. The participants who make up the team act within this process from the point of view of their appropriate professional cultures. These differences can create problems and misunderstandings, because each participant uses his own code of professional communication to defend its appraisal and point of view. And so, with the aim of improving collaborative work we suggest, in this working framework, the creation and setting up of visual tools of information exchange to facilitate innovative reasoning in the early stages of the design process. We will demonstrate that this makes it possible to bring more sense and coherence to product design, to encourage creativity and to integrate the points of view of key participants into the process, so as to generate a new product concept.